Walt Whitman and the earth : a study in ecopoetics - Killingsworth, M. Jimmie (Iowa Whitman series., 2004)
How did Whitman use language to figure out his relationship to the earth, and how can we interpret his language to reconstruct the interplay between the poet and his sociopolitical and environmental world? In this first book-length study of Whitman's poetry from an ecocritical perspective, Jimmie Killingsworth takes ecocriticism one step further into ecopoetics to reconsider both Whitman's language in light of an ecological understanding of the world and the world through a close study of Whitman's language. Killingsworth contends that Whitman's poetry embodies the kinds of conflicted experien.